2005
DOI: 10.1021/jf048646o
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Oxygen Consumption by Mitochondria and Its Effects on Myoglobin Form and Stability

Abstract: The objective of this study was to assess the morphological integrity and functional potential of mitochondria from postmortem bovine cardiac muscle and evaluate mitochondrial interactions with myoglobin (Mb) in vitro. Electron microscopy revealed that mitochondria maintained structural integrity at 2 h postmortem; prolonged storage resulted in swelling and breakage. At 2 h, 96 h, and 60 days postmortem, the mitochondrial state III oxygen consumption rate (OCR) and respiratory control ratio decreased with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(197 citation statements)
references
References 40 publications
8
179
0
10
Order By: Relevance
“…The addition of succinate can limit MetMb formation by electron transport mediated metmyoglobin reduction (Tang et al, 2005) and also by reverse electron transport (Belskie et American Meat Science Association.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of succinate can limit MetMb formation by electron transport mediated metmyoglobin reduction (Tang et al, 2005) and also by reverse electron transport (Belskie et American Meat Science Association.…”
Section: Resultsmentioning
confidence: 99%
“…Although various pre-and post-harvest factors can increase myoglobin oxidation, meat has an inherent capacity to delay metmyoglobin accumulation by a process called metmyoglobin reducing activity (MRA; Ledward, 1985). The concentration of reduced nicotinamide adenine dinucleotide (NADH), myoglobin chemistry, and mitochondrial activity play a significant role in metmyoglobin reduction (Tang et al, 2005;Ramanathan and Mancini, 2010;Nerimetla et al, 2017). In postmortem muscle, enzymes involved in the glycolytic and tricarboxylic acid cycle (TCA) retain activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiklund et al (2006) found that deer meat from animals fed pellets had a lower pH and greater a* values than the meat from grazing animals. The lower pH results in lower mitochondrial activity and lower oxygen consumption (Tang et al, 2005), which subsequently lead to rapid Mb oxygenation, increased blooming, and deeper penetration of the cherry-red OxyMb layer (Ramanathan et al, 2013).…”
Section: Feeding Managementmentioning
confidence: 99%
“…This assumption is supported by the presented TBARS results and partly by the antioxidative enzyme activities. The determination of the MRA is a method to investigate O 2 consumption of the tissue and has been analysed in muscle/meat samples from pigs (Brooks and Cassens, 1973;Campion et al, 1975;Wicke et al, 2000;Werner et al, 2010), cattle (Ashmore et al, 1972;Bendall, 1972;Lanari and Cassens, 1991;Tang et al, 2005b;Ramanathan et al, 2009) or poultry Opalka et al, 2004;Bottje and Carstens, 2009), also in relation to the muscle-tomeat transition after slaughter of the animals. Many of these studies were carried out with mitochondria isolated from the muscle/meat samples before and after slaughter.…”
Section: Discussionmentioning
confidence: 99%